Report of a Working Group on Grain Legumes: Fourth meeting, 16-17 November 2007, Lisbon, Portugal - Maggioni, L.; Lipman, E.; Bioversity International (2010)
The ECPGR Working Group (WG) on grain legumes met for its Fourth meeting in Lisbon, Portugal on 16-17 November 2007, as a Satellite meeting to the Sixth European Conference on Grain Legumes. The ECPGR Satellite meeting was attended by representatives from 17 member countries and several other observers from the Grain Legumes Conference. Review of progress was made for various crops and their databases. Issues under discussion were the need to improve safety-duplication of the collections, the urgent need for regeneration of accessions and the possible support from the Global Crops Diversity Trust. The creation of a Pisum Genetic Resources Consortium and of a Faba bean Genetic Resources International Consortium were discussed.